Analysis of the Alignment of Speech with the Requirements of Context in the Qur'an A Methodological and Foundational Study - Alsaied, Mohamad Abdullah; Farag, Hady Hussein Abdalla (Journal of Posthumanism, 2025)
This manuscript delves into one of the most revered aspects of Arabic linguistic tradition: the alignment of speech with its contextual demands. Rooted in centuries of eloquence, the Qur'an is heralded as the ultimate exemplar of this art, its verses meticulously tailored to resonate with diverse audiences across time and space. The text achieves a remarkable balance, addressing both the intellect and the emotions, and engaging individuals with varying levels of understanding. Scholars have long noted that the Qur'an’s gradual revelation—from its initial focus on creed and morality in the Meccan period to its comprehensive legislative and ethical guidance during the Medinan era—exemplifies a deliberate and context-sensitive approach to communication. This investigation draws on classical exegesis and modern rhetorical analysis to unpack the layers of meaning embedded within its verses. By scrutinizing how the Qur'an aligns its eloquent discourse with the situational requirements of its audience, this study offers fresh insights into the interplay between language and context. The research highlights how this sophisticated alignment not only reinforces the text's persuasive power but also underpins its enduring status as a source of timeless wisdom and moral clarity. Ultimately, this inquiry affirms the Qur'an’s unparalleled rhetorical mastery and enduring inspirational influence.